Diseño del procedimiento para el proceso de producción en la línea de líquidos de una empresa de productos naturales de la ciudad de Cali - Balanta Carabalí, Milton Andrés (Universidad de San Buenaventura - Cali, 2016)
The objective of this work is to design the process for the production process in the liquid line in a natural products company, applying tools to improve the ability to respond to customer requirements and ensure the delivery of goods on time. Using the tools model organizational diagnosis, data analysis and information gathering focused on collecting data to find the causes and based raizales it propose a solution to the breach in lead time. The application of this tool identified opportunities for improvement in the production process of the liquid line of the company under study, eliminating activities that did not add value to the process and the product, meeting the goals set to reduce lead time ordering of goods not delivered to customers, generating tangible benefits for the company and the end customer.